Профиль «умного» устойчивого города: НУР-СУЛТАН, КАЗАХСТАН - United Nations Economic Commission for Europe (United Nations, 2022)
This Smart Sustainable City Profile presents the outcomes of the city evaluation against the Key Performance Indicators (KPIs) for Smart Sustainable Cities (SSCs) and proposes actions to improve progress towards achieving the Sustainable Development Goals (SDGs). Based on the KPI evaluation, this profile makes a series of recommendations to further accelerate the progress of Nur-Sultan towards achieving the SDGs. They suggest improvements in areas such as solid waste management, public building sustainability, urban and spatial planning, decent-quality affordable housing, and the availability of urban data.